Combined therapy of iron chelator and antioxidant completely restores brain dysfunction induced by iron toxicity - Jirapas Sripetchwandee (2018)
Background: Excessive iron accumulation leads to iron toxicity in the brain; however the underlying mechanism is unclear. We investigated the effects of iron overload induced by high iron-diet consumption on brain mitochondrial function, brain synaptic plasticity and learning and memory. Iron chelator (deferiprone) and antioxidant (n-acetyl cysteine) effects on ironoverload brains were also studied. Methodology: Male Wistar rats were fed either normal diet or high iron-diet consumption for 12 weeks, after which rats in each diet group were treated with vehicle or deferiprone (50 mg/kg) or n-acetyl cysteine (100 mg/kg) or both for another 4 weeks. High iron-diet consumption caused brain iron accumulation, brain mitochondrial dysfunction, impaired brain synaptic plasticity and cognition, blood-brain-barrier breakdown, and brain apoptosis. Although both iron chelator and antioxidant attenuated these deleterious effects, combined therapy provided more robust results. Conclusion: In conclusion, this is the first study demonstrating that combined iron chelator and anti-oxidant therapy completely restored brain function impaired by iron overload. © 2014 Sripetchwandee et al.